A2.24 Plasma cell derived monoclonal anti-citrulline antibodies from ra synovial fluid are multireactive. (24th February 2016) - Steen, J; Sahlström, P; Ndlovu, W; Odowd, V; Israelsson, L; Alm, L Mathsson; Rapecki, S; Hansson, M; Amara, K; Klareskog, L; Lightwood, D; Malmström, V
Abstract : Background and objectives: Human recombinant monoclonal antibodies have previously been generated at our laboratory from isolated patient-derived memory B cells to assess the repertoire and specificity of human anti-citrulline antibodies. The aim of the current study was to access joint-derived antibody secreting plasma cells and explore the proportion of citrulline reactivity, the immunoglobulin mutation patterns and antigen reactivity patterns. Clearly these antibodies can be utilised as tools and can help dissect the contribution antibodies make towards disease manifestations. Materials and methods: Spontaneously IgG antibody-secreting cells (referred to as plasma cells) from synovial fluid of the inflamed joints of RA patients were isolated by a fluorescent foci method. The cells were identified and selected utilising a micromanipulator-equipped microscope. Recombinant monoclonal antibodies were generated from the isolated cells by amplification of the heavy and light chain variable antibody regions and were subsequently cloned into expression vectors. The monoclonal antibodies were screened for citrulline-reactivity by in-house ELISA or by a multiplex peptide array of RA associated antigens. Results: We generated 375 IgG sequences and 101 recombinant antibodies from both ACPA+ (n = 3) and ACPA- (n = 1) patients. Four of the antibodies from ACPA+ synovial fluid displayed strong reactivity towards a citrullinated RA antigen peptide, but not to the cognate native peptide. The antibodies were multireactive to a diverse backbone with only the citrulline residue as common denominator, however with different reactivity patterns. The majority of the anti-citrulline clones are from the VH4 gene family. We found clonality within the plasma cells (including within the anti-citrulline antibodies), but also between different B cell populations. Conclusions: Only a minority of the local plasma cells in the synovial fluid were autoreactive as measured by citrulline reactivity. However, the citrulline reactive plasma cells in the inflamed joint of RA patients where shown to be multireactive to several different citrulline peptides, with unique reactivity patterns. Further studies are needed to distinguish whether these plasma cells have differentiated locally in the joint. Still, it is tempting to speculate that the antibody characteristics that lead to multireactivity are driven by interaction towards several modified antigens, as has been suggested in the setting of influenza.